The Role of Heydar Aliyev in Protection of Our National and Moral Values - Mammadov, Jeyhun (Scholarya Demo Journal of Ruby, 2020)
The article describes the role of National Leader Heydar Aliyev in preserving the centuries-old customs and traditions, national and moral values of the Azerbaijani people and strengthening the traditions of tolerance. It underlines systematic, consistent and purposeful measures taken in our country to ensure freedom of religion, regulate relations of state and religion, strengthen the traditions of religious tolerance, protect our national and moral values and restore our religious monuments like in all spheres after his return to power. It is noted that in the first years of independence, radical religious sects, taking advantage of poor religious knowledge of the population, actively made propaganda to carry out an action regarding their goals, used various methods to gather supporters and expand their sphere of influence, and as a result, serious changes were observed in the religious situation of the country. It also describes the important decisions made by National Leader Heydar Aliyev after his return to power to reduce tensions in the sphere of religion, improve the religious situation, regulate relations of state and religion and prevent the activities of radical groups. It is stated that National Leader Heydar Aliyev regularly visited places of worship on religious holidays and remarkable days, met with religious figures, made speeches, and congratulated them on the occasion of religious holidays and ceremonies. The article underlines that Azerbaijan has become one of multiculturalism centers of the world thanks to the wise policy pursued by the President of the Republic of Azerbaijan Ilham Aliyev and First Vice President Mehriban Aliyeva, who are continuing this honorable mission initiated by National Leader with great insight and success, as such, new mosques, churches and synagogues have been built, religious educational institutions have been established in our country. It emphasizes that today Azerbaijan is recognized throughout the world as a civilized country where the traditions of tolerance are preserved, as such, tolerance is a historical achievement of our people and this factor has become the key norm of our socio-political life, our government always respects all religions and their members. The article ends with a statement that Azerbaijan benefits from the modern achievements of the West, along with maintaining its commitment to Islamic values and culture as a Muslim country, today Azerbaijan is considered as an exemplary country also in this sphere as in most other fields, one of the main goals set is to keep this tradition alive and pass it on to future generations.